2019
DOI: 10.1002/er.4770
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of residential battery storage systems and operation strategies considering battery aging

Abstract: With the increasing popularity of combining residential photovoltaic systems with battery storages, research, industry, and customers look for ways to determine if such an investment is economically profitable. Simulation programs may serve to predict the profitability and lifetime of the system. In this paper, we use techno-economic analysis with a specific account of battery degradation to determine profitability and lifetime of a residential photovoltaic (PV) battery system under different energy management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The first conclusion is that the reconfigurable BMS with BWL offers a significant improvement over the classic system, which increases as the load current decreases. This under‐load operating mode is widely used in practice, as large‐scale battery storage systems rarely operate at maximum capacity 46‐48 …”
Section: Experimental Results and Performance Analysismentioning
confidence: 99%
“…The first conclusion is that the reconfigurable BMS with BWL offers a significant improvement over the classic system, which increases as the load current decreases. This under‐load operating mode is widely used in practice, as large‐scale battery storage systems rarely operate at maximum capacity 46‐48 …”
Section: Experimental Results and Performance Analysismentioning
confidence: 99%
“…Therefore, optimum positioning capability is offered considering the physical and operational constraints of the electrical grid and heating/cooling systems. Förstl et al [ 17 ] aimed to analyze the profitability and lifecycle of a residential PV system with battery ESS based on the different tariff regimes in Australia and Germany. This study showed that the site conditions, such as geography and energy-economic conditions, have very significant impacts on the system configuration and lifetime of the battery system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the objectives of the target problem are 3-fold: first, to minimize the load curtailment to sustain the system reliability; second, to minimize the unit operation cost to make the system operation economic; and third, to minimize the wind power curtailment to make the operation more environment-friendly. These objectives are all involved in the form of the objective as (32), using the corresponding constraints shown in (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), min…”
Section: System Operation Cost Evaluationmentioning
confidence: 99%
“…Although the battery lifetime was analyzed for retired batteries using three stationary applications, energy arbitrage, autonomous use, and island installation, the method used was a direct extrapolation of existing models and, therefore, was not appropriate for the second life of batteries. The lifetime of a residential photovoltaic battery system was determined using techno‐economic analysis, but this method applied to batteries till end of life (EoL); therefore, it may not be applicable when the capacity falls to around 80% of its initial capacity, as the capacity is assumed to drop dramatically after that. On the other hand, battery manufacturers do not report data after EoL.…”
Section: Introductionmentioning
confidence: 99%